Late relapse of nonseminomatous germ cell tumor of the testis: Successful treatment with salvage chemotherapy alone - Papadimitris, C.; Papadimitriou, C.; Kokolakis, N.; Athanassiades, P.; Dimopoulos, M.A. (Urology, 1997)
Late relapses of nonseminomatous germ cell tumors of the testicle are unusual. In such cases, chemotherapy is reported to have only modest success and surgery may be the preferred treatment modality. We report a patient who experienced relapse 11 years after the initial diagnosis of advanced testicular cancer and who achieved a sustained complete remission with salvage chemotherapy alone.